2021
DOI: 10.1101/2021.03.10.434899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization and Heterotic Grouping of Traditional Assam rice (Oryza sativaL.)

Abstract: Parents of heterotic hybrids are derived from different heterotic groups with high genetic divergence. Classification of traditional Assam rice germplasm in divergent pools will be advantageous to maximize the heterosis and thereby to ensure food security. In the present investigation, a group of 60 upland rice genotypes were characterized using 53 polymorphic simple sequence repeats (SSR) markers out of 83 molecular markers. The genetic divergence study using unweighted Neighbour-joining (UNJ) method clustere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…This theory was later tested in practical hybrid breeding of different plant species. Several authors have reported in different crops no or low correlations between heterosis and the genetic distance defined by molecular markers not linked to the required trait and higher heterosis effect for a yield reported in intra-group than for inter-group hybrids [36][37][38][39]. Others stated that some significant correlations between genetically different heterotic groups formed by molecular markers and yield in hybrids were found only in particular environments and across environments [40].…”
Section: Discussionmentioning
confidence: 99%
“…This theory was later tested in practical hybrid breeding of different plant species. Several authors have reported in different crops no or low correlations between heterosis and the genetic distance defined by molecular markers not linked to the required trait and higher heterosis effect for a yield reported in intra-group than for inter-group hybrids [36][37][38][39]. Others stated that some significant correlations between genetically different heterotic groups formed by molecular markers and yield in hybrids were found only in particular environments and across environments [40].…”
Section: Discussionmentioning
confidence: 99%